PERENCANAAN KOMUNIKASI CORPORATE - Dewi, Yuni Retna (Universitas Prof. Dr. Moestopo (Beragama), 2009)
Inmany waysthissubjectisnotaneasy one,since thecorporate communicationsfunction isrelativelynew,certainlytomostEuropean companies.The resourcesputbehindcorporatecommunicationshavenotbeen asgreatasmanyhave feltdesirable,andthecommitmentofthecompany managementhasinmanycasesbeen,atbest,questionable.We areallstill learningthebest wayofapproachingthisarea,andthetenstepthatwere outlined above shouldbe taken as guiding stepsrather than a definitive approach.I havedeliberatelyavoidedreferenceinthischaptertowhatisoften known as the communications audit. I feared that to discuss the communications auditwouldinmany ways detractfromthepracticalitiesof planningthecorporatecommunicationsfunction.Theaudit,whichisdescribed elsewhere,isaveryusefulprocesstotakeaccount ofallthecommunications activitiesthatacompanyisengagedin,andassuchitshould bepartofthe overallcorporatecommunicationsplanningprocess.Indeed, theapproaches thatIhaveadvocatedareinthemselvessomefromofaudit.Thesuccessorfailureofthecommunicationsplanningprocesswillat thedayrest upon twokeyfactors: thecommitmentand energy ofthe top management,andthewillingnessofother individualstosharetheirexperience andexpertisetowardsacommoninterest.Toooften,thesefactorsaresadly missing,because thecorporate communicationsfunctioneither isnot high enoughonthechairmansagendaor,alternatively,isinconflictwhit theinterest oftheoperatingcompanies.Corporate communications planning requires determination, commonsensealittlepolitiesandagreatdealofpatience